1978
DOI: 10.1093/jn/108.12.1899
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Promotion of Bone Mineralization by 1α,25-Dihydroxycholecalciferol in the Rat Unrelated to the Correction of Deficiencies in Serum Calcium and Phosphorus

Abstract: Concurrent administration of 1alpha,25-dihydroxycholecalciferol [1alpha,25-(OH)2-CC] to intact and thyroparathyroidectomized rats treated with ethane-1-hydroxy-1,1-diphosphonate (EHDP) prevented or reversed the EHDP-induced inhibition of bone mineralization as measured by changes in epiphyseal plate width and ash content of bone. An analog, 1alpha-droxycholecalciferol, was also effective. Recovery of bone after EHDP treatment was also significantly improved by administration of 1alpha,25-(OH)2-CC as evidenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Cholecalciferol infusion has also been re ported to increase bone formation without affecting resorption in normal dogs [14] and bone collagen synthesis was found to be in creased in chickens [15] and rats [8] during healing of rickets. The failure of the low den sity calcified phase to be converted to the higher density hydroxyapatite phase in ra chitic chick bone appears to be related to the deficiency of vitamin D rather than to the accompanying disturbances in mineral me tabolism [16], Administration of 1,25-dihydroxycholecalciferol to chickens [17] or rats [18] can at least partly correct the inhibition of mineralization induced by treatment with ethane-1 -hydroxy-1,1 -diphosphonate but 24,25-dihydroxycholecalciferol was not found to be effective [18] and treatment with both dihydroxylated metabolites has been claimed to be necessary to prevent rachitic bone lesions in chickens maintained on a vitamin D-deficient diet [19], In vitro studies with these metabolites suggest that they can influence the synthesis of structural macro molecules; 1,25-dihydroxycholecalciferol has been reported to inhibit collagen synthesis in cultures of fetal rat calvaria [20] and in creased incorporation of 3SS 04 into proteo glycan was found in cultures of rabbit growth plate cells in the presence of either 1,25-or 24,25-dihydroxycholecalciferol [21],…”
Section: Introductionmentioning
confidence: 99%
“…Cholecalciferol infusion has also been re ported to increase bone formation without affecting resorption in normal dogs [14] and bone collagen synthesis was found to be in creased in chickens [15] and rats [8] during healing of rickets. The failure of the low den sity calcified phase to be converted to the higher density hydroxyapatite phase in ra chitic chick bone appears to be related to the deficiency of vitamin D rather than to the accompanying disturbances in mineral me tabolism [16], Administration of 1,25-dihydroxycholecalciferol to chickens [17] or rats [18] can at least partly correct the inhibition of mineralization induced by treatment with ethane-1 -hydroxy-1,1 -diphosphonate but 24,25-dihydroxycholecalciferol was not found to be effective [18] and treatment with both dihydroxylated metabolites has been claimed to be necessary to prevent rachitic bone lesions in chickens maintained on a vitamin D-deficient diet [19], In vitro studies with these metabolites suggest that they can influence the synthesis of structural macro molecules; 1,25-dihydroxycholecalciferol has been reported to inhibit collagen synthesis in cultures of fetal rat calvaria [20] and in creased incorporation of 3SS 04 into proteo glycan was found in cultures of rabbit growth plate cells in the presence of either 1,25-or 24,25-dihydroxycholecalciferol [21],…”
Section: Introductionmentioning
confidence: 99%
“…A deficiency of vitamin D in young growing animals results in reduced bone mineralization and diminished concentrations of calcium and phosphorus in the plasma. The failure of normal bone mineralization in vitamin D-deficient animals may largely be the result of low plasma levels of calcium and phosphorus [3][4][5], although there is some evidence that bone mineralization may be directly promoted by 1,25-dihydroxyvitamin D3 (1,25(OH)2D:0 [6][7][8].…”
mentioning
confidence: 99%
“…The present study showed that systemic administration of l,25(OH)2D 3 to young mice retarded their growth and was followed with increased levels of iPTH con comitant with a marked elevation in serum calcium con centration. In an in vivo system 1,25(0 H)2D 3 was found also to promote bone mineralization independently of the effects upon the intestinal absorption of calcium and phosphate [21]. The enhanced mineralization of bone has been related to the increase in osteoclastic bone resorption [22|, thus in an intact young animal l,25(OH)2D 3 seems to regulate bone turnover as well as mineral homeostasis.…”
Section: Discussionmentioning
confidence: 99%